Biallelic mutations in the 3' exonuclease TOE1 cause pontocerebellar hypoplasia and uncover a role in snRNA processing. - Lardelli, Rea M; Schaffer, Ashleigh E; Eggens, Veerle R C; Zaki, Maha S; Grainger, Stephanie; Sathe, Shashank; Van Nostrand, Eric L; Schlachetzki, Zinayida; Rosti, Basak; Akizu, Naiara; Scott, Eric; Silhavy, Jennifer L; et al. (Nat Genet, 2017)
Deadenylases are best known for degrading the poly(A) tail during mRNA decay. The deadenylase family has expanded throughout evolution and, in mammals, consists of 12 Mg-dependent 3'-end RNases with substrate specificity that is mostly unknown. Pontocerebellar hypoplasia type 7 (PCH7) is a unique recessive syndrome characterized by neurodegeneration and ambiguous genitalia. We studied 12 human families with PCH7, uncovering biallelic, loss-of-function mutations in TOE1, which encodes an unconventional deadenylase. toe1-morphant zebrafish displayed midbrain and hindbrain degeneration, modeling PCH-like structural defects in vivo. Surprisingly, we found that TOE1 associated with small nuclear RNAs (snRNAs) incompletely processed spliceosomal. These pre-snRNAs contained 3' genome-encoded tails often followed by post-transcriptionally added adenosines. Human cells with reduced levels of TOE1 accumulated 3'-end-extended pre-snRNAs, and the immunoisolated TOE1 complex was sufficient for 3'-end maturation of snRNAs. Our findings identify the cause of a neurodegenerative syndrome linked to snRNA maturation and uncover a key factor involved in the processing of snRNA 3' ends.
Keywords: Alleles; Animals; Cerebellar Diseases; Exonucleases; Female; Humans; Male; Mice; Mutation; Neurodegenerative Diseases; Nuclear Proteins; RNA, Messenger; RNA, Small Nuclear; Spliceosomes; Zebrafish

ALG1-CDG: Clinical and Molecular Characterization of 39 Unreported Patients. - Ng, Bobby G; Shiryaev, Sergey A; Rymen, Daisy; Eklund, Erik A; Raymond, Kimiyo; Kircher, Martin; Abdenur, Jose E; Alehan, Fusun; Midro, Alina T; Bamshad, Michael J; Barone, Rita; Berry, Gerard T; et al. (Hum Mutat, 2016)
Congenital disorders of glycosylation (CDG) arise from pathogenic mutations in over 100 genes leading to impaired protein or lipid glycosylation. ALG1 encodes a β1,4 mannosyltransferase that catalyzes the addition of the first of nine mannose moieties to form a dolichol-lipid linked oligosaccharide intermediate required for proper N-linked glycosylation. ALG1 mutations cause a rare autosomal recessive disorder termed ALG1-CDG. To date 13 mutations in 18 patients from 14 families have been described with varying degrees of clinical severity. We identified and characterized 39 previously unreported cases of ALG1-CDG from 32 families and add 26 new mutations. Pathogenicity of each mutation was confirmed based on its inability to rescue impaired growth or hypoglycosylation of a standard biomarker in an alg1-deficient yeast strain. Using this approach we could not establish a rank order comparison of biomarker glycosylation and patient phenotype, but we identified mutations with a lethal outcome in the first two years of life. The recently identified protein-linked xeno-tetrasaccharide biomarker, NeuAc-Gal-GlcNAc2 , was seen in all 27 patients tested. Our study triples the number of known patients and expands the molecular and clinical correlates of this disorder.
Keywords: Biomarkers; Congenital Disorders of Glycosylation; Female; Genes, Lethal; Glycosylation; Humans; Male; Mannosyltransferases; Mutation; Polysaccharides; Sequence Analysis, DNA; Survival Analysis